Two new species of Hymenochaetaceae from tropical Asia and America - Zhou, Meng; Ji, Xiao-Hong; Liu, Hong-Gao; Miller, Kurt; Yuan, Yuan; Vlasák, Josef (Frontiers in Cellular and Infection Microbiology, 2023)
Two new species in Hymenochaetaceae, Fulvifomes acaciae and Pyrrhoderma nigra, are illustrated and described from tropical Asia and America based on morphology and phylogenetic analyses. F. acaciae is characterized by perennial, pileate, and woody hard basidiomata when fresh; ash gray to dark gray, encrusted, concentrically sulcate, and irregularly cracked pileal surface; circular pores of 7–8 per mm with entire dissepiments; a dimitic hyphal system in trama and context; absence of setal element and presence of cystidioles; and broadly ellipsoid, yellowish brown, thick-walled, and smooth basidiospores measuring 5–6 μm × 4–5 μm. P. nigra is characterized by perennial and resupinate basidiomata with dark gray to almost black pore surface when fresh; small and circular pores of 7–9 per mm, a monomitic hyphal system with generative hyphae simple septate, hyphoid setae dominant in subiculum but not in tube trama, and absence of cystidia; and ellipsoid, hyaline, thin-walled basidiospores measuring 4–5 μm × 3–3.6 μm. The differences between the new species and morphologically similar and phylogenetically related species are discussed. Keys to Fulvifomes and Pyrrhoderma have also been provided.